Ultimate flowrate targeting with regeneration placement - Ng, Denny K.S (Animo Repository, 2007)
Water regeneration has been widely accepted as an effective mean to further reduce flowrate targets in a water network, and is often employed after the opportunity for flowrate reduction via water reuse/ recycle have been exhausted. In this work, a new numerical targeting procedure is proposed to locate the minimum regeneration flowrate that achieves the ultimate fresh water and wastewater targets for both fixed flowrate and fixed load problems. Literature examples are solved to illustrate the applicability of the developed technique. © 2007 Institution of Chemical Engineers.